A Risk Scoring System for the Prediction of Functional Deterioration, Institutionalization, and Mortality Among Medicare Beneficiaries. (October 2018) - McClintock, Heather F.; Kurichi, Jibby E.; Kwong, Pui L.; Xie, Dawei; Stineman, Margaret G.; Bogner, Hillary R.
Abstract : Objective: We sought to develop a risk scoring system for predicting functional deterioration, institutionalization, and mortality. Identifying predictors of poor health outcomes informs clinical decision-making, service provision, and policy development to address the needs of persons at greatest risk for poor health outcomes. Design: This is a cohort study with 21, 257 community-dwelling Medicare beneficiaries 65 yrs and older who participated in the 2001–2008 Medicare Current Beneficiary Survey. Derivation of the model was conducted in 60% of the sample and validated in the remaining 40%. Multinomial logistic regression model generated β coefficients, which were used to create a risk scoring system. Our outcome was instrumental activity of daily living stage transitions (stable/improved function and functional deterioration), institutionalization, or mortality for 2 yrs of follow-up. Results: A total of 18 factors were identified for functional deterioration ( P < 0.05). In the derivation cohort, the likelihood of functional deterioration ranged from 6.27% to 33.51%, risk of institutionalization from 0.07% to 12.13%, and risk of mortality from 2.13% to 31.83%, in comparison with stable/improved function. Conclusions: A risk scoring system predicting Medicare beneficiaries' risk of functional deterioration, institutionalization, and mortality based on demographic and clinical indicators may feasibly be developed with implications for healthcare delivery. Abstract : Supplemental digital content is available in the text.